The arginine-ornithine antiporter ArcD contributes to biological fitness of Streptococcus suis - Marcus eFulde (Frontiers in Cellular and Infection Microbiology, 2014)
The arginine-ornithine antiporter (ArcD) is part of the Arginine Deiminase System (ADS), a catabolic, energy-providing pathway found in a variety of different bacterial species, including the porcine zoonotic pathogen Streptococcus suis. The ADS has recently been shown to play a role in the pathogenicity of S. suis, in particular in its survival in host cells. The contribution of arginine and arginine transport mediated by ArcD, however, has yet to be clarified. In the present study, we showed by experiments using [U-13C6]arginine as a tracer molecule that S. suis is auxotrophic for arginine and that bacterial growth depends on the uptake of extracellular arginine. To further study the role of ArcD in arginine metabolism, we generated an arcD-specific mutant strain and characterized its growth compared to the wild-type (WT) strain, a virulent serotype 2 strain. The mutant strain showed a markedly reduced growth rate in chemically defined media supplemented with arginine when compared to the WT strain, indicating that ArcD promotes arginine uptake. To further evaluate the in vivo relevance of ArcD, we studied the intracellular bacterial survival of the arcD mutant strain in an epithelial cell culture infection model. The mutant strain was substantially attenuated, and its reduced intracellular survival rate correlated with a lower ability to neutralize the acidified environment. Based on these results, we propose that ArcD, by its function as an arginine-ornithine antiporter, is important for supplying arginine as substrate of the ADS and, thereby, contributes to biological fitness and virulence of S. suis in the host.